G93(P) The role of school context and family factors in bullying and cyberbullying. (27th April 2016) - Bevilacqua, L; Hale, D; Shackleton, N; Allen, E; Bond, L; Christie, D; Elbourne, D; Fitzgerald-Yau, N; Fletcher, A; Jones, R; Legood, R; Miners, A; et al.
Abstract : Background: Bullying and cyberbullying are common phenomena in schools and can have a significant impact on the health and mental health of those involved in such behaviours, both as victims and as bullies. This study aims to investigate student-level and school-level characteristics of those who become involved in bullying and cyberbullying behaviours. Methods: We used data from 6667 year-8 students from the baseline survey of a cluster randomised trial in 40 English schools. We ran multilevel models to examine associations of bullying outcomes with individual-level variables (sex, ethnicity, family composition and family socioeconomic status) and school-level variables (school-level deprivation; school type; size of student population; school sex composition (mixed or single sex school) and measures of school quality. Results: 32% of boys and 38% of girls report significant bullying victimisation, and cyberbullying victimisation was reported by 2% of boys and 4.5% of girls, with fewer (1% of boys and 0.5% of girls) reporting being cyberbullies. At the individual level, low socioeconomic status was associated with higher risk of reporting being a cyberbullying victim or perpetrator. Having a single parent was associated with increased risk of reporting being a victim of bullying or cyberbullying but not of reporting being a cyberbullying perpetrator. Being female was a risk factor for reporting being a victim of bullying or cyberbullying and a protective factor against reporting being a perpetrator of cyberbullying. At the school level, school type and school quality measures were associated with bullying risk: compared with students in converter academies mainstream, students in voluntary-aided schools were less likely to report being bullied. Students in community and foundation schools were more likely to report being perpetrators of cyberbullying. A school quality rating of "good" was associated with greater reported bullying victimisation compared to ratings of "excellent". Discussion: These results suggest that bullying and cyberbullying prevalence varies across school type and school quality, supporting the hypothesis that organisational/management factors within the school may have an impact on students' behaviour. These preliminary findings will pave the way for future research investigating in detail what are the school factors and processes that promote/prevent bullying and cyberbullying behaviours.